INNOVATIVE OPEN DATA SERVICES FOR EFFECTIVE FUNCTIONING OF е-GOVERNMENT - Klimushyn P.S.; Spasibov D.V. (Pressing Problems of Public Administration, 2017)
The principles of designing linked data have been analyzed to ensure their semantic interoperability. The problems related to opening public sector data in Ukraine are identi ed, and promising areas of developing open data services for effective functioning of e-government are presented.